Study on Competitive Adsorption and Displacing Properties of CO2 Enhanced Shale Gas Recovery: Advances and Challenges. (23rd December 2020) - Liu, Shuyang; Sun, Baojiang; Xu, Jianchun; Li, Hangyu; Wang, Xiaopu
Abstract : CO2 enhanced shale gas recovery (CO2 -ESGR) draws worldwide attentions in recent years with having significant environmental benefit of CO2 geological storage and economic benefit of shale gas production. This paper is aimed at reviewing the state of experiment and model studies on gas adsorption, competitive adsorption of CO2 /CH4, and displacement of CO2 -CH4 in shale in the process of CO2 -ESGR and pointing out the related challenges and opportunities. Gas adsorption mechanism in shale, influencing factors (organic matter content, kerogen type, thermal maturity, inorganic compositions, moisture, and micro/nano-scale pore), and adsorption models are described in this work. The competitive adsorption mechanisms are qualitatively ascertained by analysis of unique molecular and supercritical properties of CO2 and the interaction of CO2 with shale matrix. Shale matrix shows a stronger affinity with CO2, and thus, adsorption capacity of CO2 is larger than that of CH4 even with the coexistence of CO2 -CH4 mixture. Displacement experiments of CO2 -CH4 in shale proved that shale gas recovery is enhanced by the competitive adsorption of CO2 to CH4 . Although the competitive adsorption mechanism is preliminary revealed, some challenges still exist. Competitive adsorption behavior is not fully understood in the coexistence of CO2 and CH4 components, and more experiment and model studies on adsorption of CO2 -CH4 mixtures need to be conducted under field conditions. Coupling of competitive adsorption with displacing flow is key factor for CO2 -ESGR but not comprehensively studied. More displacement experiments of CO2 -CH4 in shale are required for revealing the mechanism of flow and transport of gas in CO2 -ESGR.